Heterogeneity of CD8αα intraepithelial lymphocytes is transcriptionally conserved between TCRαβ and TCRγδ cell lineages - Hioki, Kaito A.; Liang, Xueting; Lynch, Adam C.; Ranjan, Ravi; Pobezinskaya, Elena L.; Pobezinsky, Leonid A. (Frontiers in Immunology, 2025)
Intestinal intraepithelial lymphocytes (IELs) are a versatile population of immune cells with both effector and regulatory roles in gut immunity. Although this functional diversity is thought to arise from distinct IEL subpopulations, the heterogeneity of TCRαβ+ and TCRγδ+ IELs have not been well characterized. Using scRNAseq, we identified CD8αα+ T cell subsets with memory-like (Tcf7+) and effector-like (Prdm1+) profiles in both TCRαβ+ and TCRγδ+ IELs. Using CD160 and CD122 as markers of memory-like and effector-like cells, respectively, we found that while effector-like cells dominated the small intestine, memory-like IELs were more prevalent in the large intestine, suggesting a functional specialization of immune responses along the gut. Further transcriptional analysis revealed shared profiles between TCRαβ+ and TCRγδ+ small intestinal IEL subsets, suggesting conserved functional roles across these populations. Finally, our analysis indicated that TCRαβ+ memory-like IELs arise from Tcf7+ double-negative (DN) precursors, and that effector-like IELs subsequently differentiate from the memory-like population. In contrast, TCRγδ+ IELs appear to originate from two distinct precursor populations, one expressing Tcf7 and the other Zeb2, indicating the presence of parallel developmental pathways within this lineage. Overall, our findings reveal that both TCRαβ+ and TCRγδ+ cells contain memory-like and effector-like subsets, which may contribute to the functional heterogeneity of IELs.